Perl one-liners : 130 programs that get things done - Krumins, Peteris (No Starch Press, 2014)
"Perl one-liners are small and awesome Perl programs that fit in one line of code and do one thing really well. Perl One-Liners showcases 130 short and compelling lines of code that do all sorts of handy, geeky things like numbering lines in a file; generating random passwords; encoding, decoding, and converting strings; calculating factorials; even checking to see if a number is prime with a regular expression. Author Peteris Krumins' dissections of each bit of code will help you gain a deeper understanding of the Perl language, and these Perl one-liners are sure to save you time and sharpen your sleight of hand"--